Application of Hyaluronic Acid for Treatment of Interdental Papillary Deficiency: A Systematic Review and Meta-Analysis - Jowel Makdisi; solmaz akbari; Farid Zayeri; Hoori AslRoosta; Siamak Yaghobee (Tehran University of Medical Sciences, 2023)
Objectives: The focused question of this systematic review was "does hyaluronic acid (HA) injection in areas of interdental papillary deficiency reduce black triangles?" Materials and Methods: A systematic literature search was performed to find clinical studies on human patients with a minimum of 6-month follow-up, published in English from 2005 to May 2020. There were two outcome variables: black triangle area (BTA) change after treatment at different measurement time points compared with baseline, and patient reported outcome measures (PROMs), when available. Results: Of eight eligible articles (2 randomized clinical trials (RCTs) and 6 non-randomized, non-placebo controlled clinical studies), seven reported that HA injections had a positive impact on reduction of BTA and subsequent papillary augmentation. Six studies were included in meta-analysis and showed that the intervention led to a pooled reduction percentage of 57.7% in BTA after 6 months. Although there were clinical diversities between the studies, all the studies applied the same concentration of HA (approximately 2%), 2-3 mm apical to the papilla tip in several intervals. Some degrees of relapse were reported in some studies. Conclusion: Within the limits of this study, this systematic review and meta-analysis showed that HA injection can serve as an efficient minimally-invasive treatment for small interdental papillary deficiencies. It is essential to conduct further randomized clinical studies with prolonged follow-ups in order to support this conclusion.